KEMAMPUAN MEMAHAMI UNSUR INTRINSIK TEKS DRAMA SISWA KELAS VIII MTS MUHAMMADIYAH DESA PENYASAWAN KECAMATAN KAMPAR - Rapika Sundari; Nursal Hakim; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purposes of this research is to describe the ability in comprehend the element of intrinsic in drama of second year student at MTs Muhammadiyah Penyasawan village Kampar district. The element of intrinsic is element which develop build belleslettres from within. The element of intrinsic is an important elemen whick is supposed to be learned by students in learning literature. In learned literature at school, comprehend the element of intrinsic in drama is one of basic component that should be learned at second grade of MTs. This research is aimed to know the students’ ability in comprehend the element of intrinsic in drama of second year student at MTs Muhammadiyah Penyasawan village Kampar district. Generally, there are 5 element of intrinsic are those theme, plot, characteristic, setting, and moral message. In this research, the method that’s used is descriptive method with 50 samples. To collect the data, the researcher collected the students’ test result, gave score, found the percentage of each element, and considered the average score. The resul can be concluded that the students’ ability in understanding the element of intrinsic in drama of second year students at MTs Muhammadiyah Penyasawan village Kampar district are categorized as low with average score 67. Percentage of high ability level student was 8%, medium 32%, and low 60%. The detail of average score of intrinsic element that has obtained is that: theme was categorized as low (46), plot was categorized as high (94), characteristic was categorized as low (66), setting was categorized as medium (79), moral message was categorized as low (50).Keywords: element intrinsic,text drama, theme, moral message plot, characteristic, and setting.